2020
DOI: 10.1016/j.eujim.2020.101226
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in patients with COVID-19–a systematic review

Abstract: Introduction In the current COVID-19 pandemic, disease diagnosis is essential for optimal management and timely isolation of infected cases in order to prevent further spread. The aim of this study was to systematically review the assessment of risk and model the predictors of mortality in COVID-19 patients. Methods A systematic search was conducted of PubMed, Scopus, Embase, Google Scholar, and Web of Science databases. Variables associated with hospital mortality usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
127
2
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 156 publications
(156 citation statements)
references
References 30 publications
11
127
2
3
Order By: Relevance
“…The LASSO multivariate analysis found age, number of comorbidities, extension of ground glass opacities on chest CT and troponin with a direct relationship with all-cause mortality, whereas dysgeusia, use of angiotensin converting enzyme inhibitor or angiotensin-ii receptor blocker and number of lymphocytes with an inverse relationship with all-cause mortality In different studies older age, hypertension, diabetes melitus, dyspnea, number of comorbidities, and laboratory parameters were associated to increased risk of mortality in patients with COVID-19 [ 28 , 29 ]. The symptoms at presentation in our study were not significantly different compared with those of other large studies [ 16 , 30 ], even considering that our patients had, on average, more severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…The LASSO multivariate analysis found age, number of comorbidities, extension of ground glass opacities on chest CT and troponin with a direct relationship with all-cause mortality, whereas dysgeusia, use of angiotensin converting enzyme inhibitor or angiotensin-ii receptor blocker and number of lymphocytes with an inverse relationship with all-cause mortality In different studies older age, hypertension, diabetes melitus, dyspnea, number of comorbidities, and laboratory parameters were associated to increased risk of mortality in patients with COVID-19 [ 28 , 29 ]. The symptoms at presentation in our study were not significantly different compared with those of other large studies [ 16 , 30 ], even considering that our patients had, on average, more severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies reported hypertension as an independent predictor of hospitalization, an advanced stage of pneumonia, admission to the intensive care unit (ICU), and mortality in these patients ( 3 5 ). Later investigations raised the question whether hypertension would be a predictor of outcome in COVID-19 patients independently of diabetes, obesity, and other cardiovascular diseases ( 6 , 7 ). Furthermore, the majority of studies did not make any distinction between patients with chronic and new-onset of hypertension in COVID-19 patients, which could significantly impact final results.…”
Section: Introductionmentioning
confidence: 99%
“…As of February 9 th , 2021, there were more than 106 million confirmed infections and >2.3 million deaths, worldwide (WHO Coronavirus Disease (COVID-19) Dashboard, 2020), making this ongoing disease the deadliest pandemic of the 21 st century. Clinical manifestations of SARS-CoV-2 infection can range from asymptomatic (Nishiura et al, 2020) and mild upper airway symptoms to severe lower respiratory complications such as pneumonia, acute respiratory distress syndrome (ARDS), and multi-organ system dysfunction (Huang et al, 2020a), leading to respiratory compromise (Giamarellos-Bourboulis et al, 2020) and death (Mehraeen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%